Social studies teachers' knowledge and criteria for selecting and utilizing instructional materials in teaching and learning - Bordoh, Anthony (Frontiers in Education, 2025)
IntroductionThis study explored the understanding and application of principles for selecting and using instructional materials by Social Studies teachers in Senior High Schools within the Mfantsiman Municipality. The study was grounded in the ASSURE model.MethodsQualitatively, a literal replication multiple case study research design was employed. The study population consisted of Social Studies teachers from three selected schools, and a sample of eight teachers were included. The data were gathered through interviews and analyzed thematically.Results and discussionThe study revealed that the teachers' awareness of instructional material principles reflects their ability to align these materials with student needs and instructional objectives, indicating a strong foundational knowledge base essential for effective teaching and learning of Social Studies. The teachers' material selection aligns well with curriculum objectives and student needs; however, this process often relies on subjective judgment rather than standardized evaluative tools, which could lead to inconsistencies in instructional quality. Professional Learning Community meetings should strengthen teachers' understanding of selecting and using instructional materials effectively, emphasizing their practical application in diverse classroom settings. Social Studies teachers are also recommended to develop guidelines and checklists to standardize the selection of instructional materials, incorporating inclusivity, cultural sensitivity, subject matter, and resource availability as key criteria.